Dual-Career Couples: The Juggling Act - Neault, Roberta A.; Pickerell, Deirdre A. (Canadian Journal of Counselling and Psychotherapy, 2007)
For couples with two professional careers, juggling work and home responsibilities has never been easy. However, in today’s global economy, where local job opportunities may be harder to find, new challenges are emerging. Is it possible to have a successful career without sacrificing personal satisfaction, life balance, or relationships? A literature review and exploratory conversations with dual-career couples revealed numerous challenges that impact work, home and family, and personal well-being. Success strategies reported by several dual-career couples are presented. Counselling interventions that address role conflict, relationship strengthening, financial concerns, time management, stress management, and work-life balance are recommended.